4(b-2)=2(b-6)

Simple and best practice solution for 4(b-2)=2(b-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(b-2)=2(b-6) equation:


Simplifying
4(b + -2) = 2(b + -6)

Reorder the terms:
4(-2 + b) = 2(b + -6)
(-2 * 4 + b * 4) = 2(b + -6)
(-8 + 4b) = 2(b + -6)

Reorder the terms:
-8 + 4b = 2(-6 + b)
-8 + 4b = (-6 * 2 + b * 2)
-8 + 4b = (-12 + 2b)

Solving
-8 + 4b = -12 + 2b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-2b' to each side of the equation.
-8 + 4b + -2b = -12 + 2b + -2b

Combine like terms: 4b + -2b = 2b
-8 + 2b = -12 + 2b + -2b

Combine like terms: 2b + -2b = 0
-8 + 2b = -12 + 0
-8 + 2b = -12

Add '8' to each side of the equation.
-8 + 8 + 2b = -12 + 8

Combine like terms: -8 + 8 = 0
0 + 2b = -12 + 8
2b = -12 + 8

Combine like terms: -12 + 8 = -4
2b = -4

Divide each side by '2'.
b = -2

Simplifying
b = -2

See similar equations:

| 7x-(4x-6)=30 | | 6r-(-2r-27)=21 | | 19-4c= | | 18=10+4x+4 | | 6y-2=14y+62 | | 7x+9=-29 | | 9=x-3 | | 6y-2=14y+64 | | 3h+1=3(h+1) | | 7x-7=49 | | 2(x-1)-3(x+2)=8 | | 8(12)-18=n | | y=.03x+200 | | -6x-1=-1 | | 3(x-5)=6(x-6) | | 14x+23=-93 | | 7x+3(4x-1)=49 | | 12-8x-6=-13x+21 | | -3x-10=-10 | | 2x-4+x=8 | | (4x-7)-(2x-2)= | | -7x+5=-58 | | 64=8r+2 | | 7h=9.1 | | (2x+5x)=20 | | 6n-10=4n-2 | | 7x+2=4x+15 | | (49y)-2m=180 | | 3(x+2)=2(2x+5) | | 60+n+6=75 | | (3y+4y)*2-2m=180 | | 5(x+2)=4(2x+1) |

Equations solver categories